PKM Pemberdayaan Pemandu Lingkungan dan Katekis: Workshop Peran Spiritualitas Katekis dalam Pengembangan Formatio Iman Berjenjang di Paroki Santo Krisologus BSB Semarang - FR. Wuriningsih; Gregorius Daru Wijoyoko (Lembaga Pengembangan Kinerja Dosen, 2024)
Community Service Activities (PKM) carried out at St. Peter Krissologus Parish BSB aims to strengthen the spirituality and pastoral skills of catechists through a principle-based approach of